Heat-Shock Triggers Inverted Induction of Hypo-S-Nitrosylation and Hyper-O-GlcNAcylation - Kim, Min-Jae; Ryu, In-Hyun; Do, Su-Il (Protein and Peptide Letters, 2022)
Introduction: Protein S-nitrosylation (SNO) and O-GlcNAcylation are important posttranslational modifications. The biological connection between SNO and O-GlcNAcylation is not clear. Objective: We aim to identify the crosstalk between SNO and O-GlcNAcylation during heat-shock. Methods: Ex vivo heat-shock on mouse tissues together with in vitro heat-shock on culture cells was performed and global levels of SNO and O-GlcNAcylation were analyzed with Biotin-switch assay (BSA) and RL2 immunoblots. Results: Heat-shock induces hypo-SNO in parallel with hyper-O-GlcNAcylation. Inverted induction of hypo-SNO and hyper-O-GlcNAcylation is globally progressed in a time-dependent manner. Discussion: Moreover, heat-shock ubiquitously facilitates S-denitrosylation (SdeNO) of endogenous SNO-proteins including SNO-OGT, SNO-Hsp70, SNO-Hsp90, SNO-Akt, and SNOactin. Particularly, SdeNO of SNO-OGT leads to enhanced OGT activity. Conclusion: These findings provide mechanistic evidence that heat-shock triggers SdeNO of SNOOGT by which OGT activity is up-regulated, resulting in hyper-O-GlcNAcylation.
Keywords: O-GlcNAcylation